In situ one step synthesis of Fe inserted octaethylporphyrin/polyindole: A multifunctional hybrid material with improved electrochemical and electrical properties - Verma C.J.; Pandey R.K.; Prakash R. (My University, 2025)
We report a facile and novel methodology for synthesis of Fe(II)-octaethylporphyrin/polyindole (Fe-OEP/PIn) hybrid material for electronic and electrochemical applications. The novelty of the work lies in coordination of iron in the OEP cavity and polymerization of indole monomer in a single step at room temperature. The ferric chloride used as oxidizing agent for polymerization of indole and the reduced Fe(II) ions are allowed to occupy the OEP cavity due to strong attraction of Fe(II) state towards porphyrinic cavity. The as synthesised hybrid materials are characterized and further used for fabrication of Schottky diode using a sandwiched structure Al/Fe-OEP-PIn/ITO which shows 0.21 cm2/Vs mobility, 2.1 ideality factor, and 0.60 eV barrier height. The improvement in electrochemical and electronic properties is discussed taking into account of outcome of various characterizations. Our study demonstrates the facile and novel synthesis of Fe-OEP/PIn hybrid material and its electrochemical and organic device applications. © 2017